Manejo del COVID-19: Granjas de frutas y verduras, y empacadoras - Laurel Dunn; Michelle D. Danyluk (EDIS)
This is the Spanish-language translation of FSHN20-25/FS366: Handling COVID-19: Produce Farms and Packinghouses. This material is adapted from the version published at https://foodsafety.ces.ncsu.edu/covid-19-resources/. Written by Laurel Dunn and published by the UF/IFAS Food Science and Human Nutrition Department, February 2021.